Disordered eating measures validated in pregnancy samples: a systematic review. Issue 4 (4th July 2021) - Bannatyne, Amy Jean; McNeil, Elyse; Stapleton, Peta; MacKenzie-Shalders, Kristen; Watt, Bruce
ABSTRACT: Although disordered eating in pregnancy has been linked to numerous negative consequences, there is currently no published instrument specifically devised to identify or measure such symptoms in pregnancy. As such, this study systematically reviewed the literature to evaluate the performance of general measures of disordered eating in pregnancy samples. A systematic search of the following electronic databases was undertaken from inception to April 2019: Scopus, Medline, PsycINFO, Embase, ProQuest Dissertations and Theses, and the Cumulative Index to Nursing and Allied Health Literature. From 1724 citations, eight publications met the inclusion criteria and were included in the review. Most of the included studies (6/8) were of reasonable quality. Overall, three self-report inventories (EDE-Q, EDI-2, and DEBS) and one semi-structured clinical interview (EDE) had some form of psychometric information available. Most studies reported reliability, with only two reporting validity. No studies assessed screening accuracy. Other than the EDE-Q, which had preliminary evidence to suggest possible utility in pregnancy, the findings of this review revealed little to no evidence to support the use of general measures of disordered eating in pregnancy. A strong need for research exploring the validity of existing measures in pregnancy samples, including the EDE-Q, was also evident.